دراسة تأثير استبدال حصويات المونة بالبوزولانا الطبيعية على خصائصها الطرية والصلبة - خيربك علي; الجبيلي نسرين (Latakia University Journal -Engineering Sciences Series, 2014)
يتناول هذا البحث دراسة إمكانيةِ إنتاجِ مونةٍ إسمنتية خفيفة الوزن بمقاومة على الضغط البسيط تتراوح بين (170-400kg/cm2) وبكثافة أقل من 1920kg/m3 تسمح باعتماد تسمية المونة الخفيفة، وذلك باستخدام مادة البوزولانا الطبيعية كحصويات ناعمة. تهدف الدراسة المجراة إلى استبدال حصويات المونة الإسمنتية المتمثلة بالرمل السيليسي بحصويات خفيفة من البوزولانا الطبيعية. فتم اعتماد قيم الاستبدال كنسب مئوية من حجم الرمل المستخدم في المونة (0, 10, 20, 30 50, 100%). وتم اختبار الخصائص الريولوجية للمونة الطرية والمتمثلة بقابلية التشغيل، وقياس المقاومة على الضغط البسيط، المقاومة على الشد بالانعطاف، والوزن الحجمي، ونسبة الامتصاص الأعظمي للماء في الحالة الصلبة. فسمحت النتائج بإيجاد علاقات تربط بين مجمل هذه الخصائص ونسب استبدال الرمل بالبوزولانا الطبيعية؛ حيث بينت النتائج أن استخدام البوزولانا الطبيعية كبديل عن الرمل السيليسي يقدم مجموعة من الميزات أهمها الإقلال من كثافة المونة ومن ثم إنتاج مونةٍ خفيفة يمكن استخدامها في العناصر الإنشائية عندما تزيد مقاومتها على الضغط البسيط عن.170kg/cm2 This research deals with the study of the possibility of producing lightweight cement mortar with simple compressive strength in range of (170-400kg/cm2) and density less than 1920kg/m3 allow the adoption of a lightweight mortar label, by using normal pozzolana as fine aggregates. The study aims to replace the silica sand of cement mortar with lightweight aggregates of natural pozzolana, replacement values was adopted as a percentage of the size of the sand used in the mortar (0, 10, 20, 30, 50, 100%). Rheological properties were tested for fresh mortar which means the ability of working, and measuring simple compressive strength, flexural strength, volumetric weight, and the rate of maximum absorption of water in the hardened state. Results allowed to find relationships between all of these properties and replacement ratios the silica sand with natural pozzolana. The results showed that using natural pozzolana as a replacement of silica sand offers a range of features including reducing the density and thus the production of lightweight mortar which can be used in the structural elements when its compressive strength is more than 170kg/cm2.